2019
DOI: 10.1017/s0033291719001521
|View full text |Cite
|
Sign up to set email alerts
|

Do neighborhood social processes moderate the etiology of youth conduct problems?

Abstract: BackgroundPrior work has robustly suggested that social processes in the neighborhood (i.e. informal social control, social cohesion, norms) influence child conduct problems (CP) and related outcomes, but has yet to consider how these community-level influences interact with individual-level genetic risk for CP. The current study sought to do just this, evaluating neighborhood-level social processes as etiologic moderators of child CP for the first time.MethodsWe made use of two nested samples of child and ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 64 publications
2
20
0
Order By: Relevance
“…Instead, its etiology appeared to remain constant regardless of the level of disruption, consistent with research implicating ADHD as a neuropsychiatric diagnosis primarily subject to genetic influences (e.g., 31). These null findings are unlikely to be a function of low statistical power, since prior GxE data simulations ( 32 ) have indicated that researchers have substantial power to detect E moderation in particular. Thus, despite the significant phenotypic association between disruption and scores on hyperactivity/inattention, disruption does not appear to moderate its non-shared environmental etiology.…”
Section: Discussionmentioning
confidence: 93%
“…Instead, its etiology appeared to remain constant regardless of the level of disruption, consistent with research implicating ADHD as a neuropsychiatric diagnosis primarily subject to genetic influences (e.g., 31). These null findings are unlikely to be a function of low statistical power, since prior GxE data simulations ( 32 ) have indicated that researchers have substantial power to detect E moderation in particular. Thus, despite the significant phenotypic association between disruption and scores on hyperactivity/inattention, disruption does not appear to moderate its non-shared environmental etiology.…”
Section: Discussionmentioning
confidence: 93%
“…First, this sample is only moderately sized by current twin study standards. However, power analyses (Burt, Clark, Pearson, Klump, & Neiderhiser, 2020; Purcell, 2002) suggest that it may be adequate, particularly since we focused on a reduced AE model. Second, though our enrichment strategy for families from lower‐income neighborhoods was successful, and we used a strong sampling frame from birth records, we did not use sample weights.…”
Section: Discussionmentioning
confidence: 99%
“…Neighborhood disadvantage as measured by the ADI is correlated with poorer physical (Kind et al, 2014; Powell et al, 2020) and mental (Burt et al, 2020) health, as well as higher BMI (Sheets et al, 2020) and lower physical activity (Miller et al, 2021). The ADI also has excellent internal consistency (α = .95 in past research; Singh, 2003).…”
Section: Methodsmentioning
confidence: 99%